Traumatic dental injury among rural school children in Nigeria - Obehi O. Osadolor (Advances in Medical, Pharmaceutical and Dental Research)
Background: Traumatic dental injury is a condition of dental public health interest as it can affect quality of life of children with affected teeth. Objective: To determine the prevalence, place of injury, causes of injury and pattern of presentation of traumatic dental injury among rural public school children aged 12 – 15 years in four south-eastern Nigerian communities.  Methodology: A cross sectional descriptive study of 12-15 years old school children was done in rural public schools selected in Nkanu–West and Udi local Government Area of Enugu State. Statistical analysis was done using SPSS Version 25. P values < 0.05 were accepted as being statistically significant. Results: One hundred and twenty nine (47.4%) males, one hundred and forty three (52.6%) females were seen and examined. The mean age of the children was 13.5 ± 1.1 years. The prevalence of traumatic dental injury was 3.7%. Traumatic dental injury occurred as a result of fall, mostly at home and no gender difference between males and females was seen. Enamel with dentine fracture was the most common presentation with single tooth fracture presentation higher than multiple teeth fracture. Conclusion: The prevalence of traumatic dental injury was low. Traumatic dental injury occurred as a result of fall, mostly at home and uncomplicated crown fracture was the presentation seen. A visit to dental clinic for clinical assessment and treatment is recommended.